The modified reliability-based iterative majority-logic decoding algorithm for structured LDPC codes - Chen, Haiqiang; Li, Jinfeng; Qin, Tuanfa (2011 International Conference on Electronic and Mechanical Engineering and Information Technology, 2011)
In this paper, we present a modified reliability-based iterative majority-logic decoding (MRBI-MLGD) algorithm for structured LDPC codes. The MRBI-MLGD algorithm uses the initial rather than the last updated message value in the iteration procedure, which works resembling a turbo decoder. Furthermore, the MRBI-MLGD algorithm is an integer message passing algorithm and mainly requires logical and integer operations. Simulation results show that, compared to the original one, the MIRB-MLGD algorithm can achieve better performance with slightly increased computational complexity.